An assessment of natural and manmade hazard effects on the underwater light field of the Doce River continental shelf - Oliveira Coimbra, Keyla Thayrinne; Alcantara, Enner [UNESP]; Souza Filho, Carlos Roberto de (Elsevier B.V., 2019)
Natural and manmade disasters have occurred more frequently due mainly to climate change and human pressure for productivity. One of the world's vastest disasters in the mining industry occurred due to the collapse of the Fundao dam, Brazil, which discharged about 43 million m(3) of iron tailings at the Doce River basin. Extreme natural events also affect this region and provoke substantial mass movement and substantial floods in the Doce River basin, and flow of anomalous volumes of sediments in its mouth. The extent of tailings and the sediment flow in these events were approached in previous research. However, their effects on the penetration of sunlight into the water column in the coastal region are unknown. Here, we evaluate the effects of an extreme natural event and a manmade disaster on the light regime of the water column at the Doce River mouth, using remote sensing data. In both events, the spatial and temporal distribution of suspended particulate matter (SPM), diffuse light attenuation coefficient (K(cl)490) and Euphotic Zone (Z(eu)) were analyzed. During the natural event light penetration into the water column was strongly attenuated (K d 490: 0.35 m(-1); SPM: 8.81 g/m(3)) but re-established after 1 month due to sediment deposition. In the case of the dam collapse, the attenuation of light penetration was also intense along the event (K(d)490: 0.34 m(-1); SPM: 13.87 g/m(3)); however, sediment deposition occurred sooner. Re-suspension of sediments due to wind action was recurrent after 8 months of the dam collapse, in contrast to the natural event where re-suspension was not perceptible in satellite images. The results indicate that both events have considerable effects on the penetration of light in the water column, but with different intensity and length. (C) 2019 Published by Elsevier B.V.
Keywords: Natural and manmade disasters; Bio-optical properties; Fundao tailing dam; Euphotic zone; Light attenuation